Chronic diseases and determinants of community health services utilization among adult residents in southern China: a community-based cross-sectional study - Junwang Gu; Qi Wang; Wei Qiu; Chunmei Wu; Xiaoqiang Qiu (BMC, 2024)
Abstract Background The burden of chronic diseases has become a major public health concern, and high-efficiency use of community health services is essential in combating chronic diseases. This study described the status of chronic diseases in southern China and explored the determinants of health service utilization among adult residents. Methods Data were obtained from one part of community survey data from four counties in Ganzhou City, southern China. A multistage, stratified random sampling method was used to conduct a cross-sectional survey between 2018 and 2020. Overall, 7430 valid questionnaires were collected. A lasso-linear regression analysis was performed to explore the determinants of community health service utilization. Results According to the study, most participants (44.6%) reported having relatively good health, while 42.1% reported having moderate health. Chronic diseases were reported by 66.9% of the respondents. The three most prevalent self-reported chronic diseases were hypertension (22.6%), hyperlipidemia (5.9%), and diabetes (5.9%). Among residents with chronic diseases, 72.1% had one chronic disease, while the rest had multiple. Only 13.9% of residents frequently utilized community health services, while 18.9% never used them. Additionally, among residents who reported having chronic diseases, 14.1% had never attended community health services. Four categories of factors were the key determinants of community health service utilization: (1) personal characteristics, age, and sex; (2) health-related factors, such as family history, self-reported health conditions, and the number of chronic diseases; (3) community health service characteristics, such as satisfaction with and accessibility to community health services; and (4) knowledge of chronic diseases. Specifically, women tend to utilize healthcare services more frequently than men. Additionally, residents who are advanced in age, have a family history of chronic diseases, suffer from multiple chronic conditions, rate their self-reported health condition as poor, have a better knowledge about chronic diseases, have better accessibility to community health services, and have higher the satisfaction with community health services, tend to utilize them more frequently. Conclusions Given the limited healthcare resources, the government should promote the effective utilization of community health facilities as a critical community-based strategy to combat the growing threat of chronic diseases in southern China. The priority measures involve enhancing residents' access to and satisfaction with community health services and raising awareness of chronic illnesses among older individuals with poor health status.